2015
DOI: 10.1128/mcb.01206-14
|View full text |Cite|
|
Sign up to set email alerts
|

Brk/Protein Tyrosine Kinase 6 Phosphorylates p27KIP1, Regulating the Activity of Cyclin D–Cyclin-Dependent Kinase 4

Abstract: Cyclin D and cyclin-dependent kinase 4 (cdk4) are overexpressed in a variety of tumors, but their levels are not accurate indicators of oncogenic activity because an accessory factor such as p27Kip1 is required to assemble this unstable dimer. Additionally, tyrosine (Y) phosphorylation of p27 (pY88) is required to activate cdk4, acting as an "on/off switch." We identified two SH3 recruitment domains within p27 that modulate pY88, thereby modulating cdk4 activity. Via an SH3-PXXP interaction screen, we identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 55 publications
(66 reference statements)
2
42
0
Order By: Relevance
“…During interphase, the G1-S transition is a critical restriction point, resulting in one of three fates for the cell: continue cycling, exit active proliferation, or enter a quiescent (G0) state. Many growth factors and inhibitors interact to coordinate cell cycle progression, and the CDK4/6-Rb pathway (5,6) plays a central role in regulating the G1 to S phase transition. So far, 21 cyclin-dependent kinases (CDKs) have been identified in mammalian cells by the HUGO Gene Nomenclature Committee (HGNC) and the Mouse Genomic Nomenclature Committee (7).…”
Section: Cdks and Cell Cycle Regulationmentioning
confidence: 99%
“…During interphase, the G1-S transition is a critical restriction point, resulting in one of three fates for the cell: continue cycling, exit active proliferation, or enter a quiescent (G0) state. Many growth factors and inhibitors interact to coordinate cell cycle progression, and the CDK4/6-Rb pathway (5,6) plays a central role in regulating the G1 to S phase transition. So far, 21 cyclin-dependent kinases (CDKs) have been identified in mammalian cells by the HUGO Gene Nomenclature Committee (HGNC) and the Mouse Genomic Nomenclature Committee (7).…”
Section: Cdks and Cell Cycle Regulationmentioning
confidence: 99%
“…5). An [78]. This is suggestive of another potential mecha-641 nism by which BRK contributes towards mammary oncogenesis [78].…”
mentioning
confidence: 90%
“…Lately, p27Kip1 was reported as another novel substrate of BRK[78]. It was shown that p27Kip is recruited to the BRK SH3 domain and is phosphorylated on Y74, Y88 and Y89, which was suggested as a mechanism via which BRK promotes cell cycle progression[78].In a relatively recent discovery, heat shock protein 90 (Hsp90) was established as the major protein responsible for regulating endogenous BRK stability in the T47D and BT474 breast carcinoma cell lines[60].…”
mentioning
confidence: 99%
“…Other suggested mechanisms of de novo resistance to CDK4/6 inhibitors, involving deregulation of cell cycle-related proteins, include phosphorylation status of p27 and fizzy-related protein homolog (FZR1) [29,30]. In addition to its ability to inhibit cyclin D/CDK4, p27 can regulate the cyclin D/CDK4/p27 ternary complex activity depending on phosphorylation status of tyrosine Y74, Y88, and Y89, [31].…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…In addition to its ability to inhibit cyclin D/CDK4, p27 can regulate the cyclin D/CDK4/p27 ternary complex activity depending on phosphorylation status of tyrosine Y74, Y88, and Y89, [31]. It was shown that overexpression of Brk (breast tumor-related kinase), an intracellular tyrosine kinase overexpressed in 60% of breast cancers [32], increases phosphorylation on Y88 of p27 and cyclin D/CDK4 activity, rendering breast cancer cells more resistant to palbociclib [29]. …”
Section: Mechanisms Of Resistancementioning
confidence: 99%